Financial soundness indicators compilation guide - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2019)
The 2019 Financial Soundness Indicators Compilation Guide (2019 Guide) includes new indicators to expand the coverage of the financial sector, including other financial intermediaries, money market funds, insurance corporations, pension funds, nonfinancial corporations, and households. In all, the 2019 Guide recommends the compilation of 50 FSIs—13 of them new. Additions such as new capital, liquidity and asset quality metrics, and concentration and distribution measures will serve to enhance the forward-looking aspect of FSIs and contribute to increase policy focus on stability of the financial system. (IMF page)
1. Introduction -- 2. Institutional Sectors and the Financial System -- 3. Basel Capital and Liquidity Standards for Deposit Takers -- 4. Accounting Principles for Financial Soundness Indicators -- 5. Sectoral Financial Statements for Financial Soundness Indicators -- 6. Aggregation and Consolidation of Data -- 7. Specification of Core Financial Soundness Indicators for Deposit Takers -- 8. Specification of Additional Financial Soundness Indicators for Deposit Takers -- 9. Specification of Financial Soundness Indicators for Other Financial Corporations -- 10. Specification of Financial Soundness Indicators for Nonfinancial Sectors -- 11. Compilation and Dissemination of Financial Soundness Indicators -- 12. Concentration and Distribution Measures -- 13. Financial Soundness Indicators and Macroprudential Analysis
includes bibliographical references (P:181-186) and index.
Keywords: International banking; FINANCIAL INSTITUTIONS; AUDITING; ECONOMIC INDICATORS; MANUALS; IMF